Negotiation: How Indonesia Use Its Power Based Position towards Freeport Mining Industry - Siciliana Agave SIhombing; Cecep Safa'atul Barkah; Nurillah Jamil Achmawati Novel (JURNAL BISNIS STRATEGI, 2022)
The problems studied in this study include: first, what is Indonesia's position in the Freeport Contract of Work? Second, how does Indonesia use its power-based position to win this renegotiation? Third, how is the progress of implementing renegotiation as a solution to the problems posed by the Contract of Work? This research was conducted using a library research method through a conceptual approach and a social approach. The results show that: Indonesia's position in the Kontrak Karya is equivalent to Freeport, same as the position of the parties in a contract. Second, Indonesia uses its power as an independent country by creating the IUPK Law and prohibiting the export of mineral concentrates to narrow Freeport's movement. Third, Indonesia proposed renegotiation for its losses arising from the operation of Freeport in Indonesia, but the renegotiation was difficult to reach the expected agreement because it was contradict with the principle of pacta sunt servanda. After a long negotiation process, a mutually beneficial decision was reached for both parties.